Synthesis and Characterization of Mn(II), Ni(II), Cu(II), Zn(II) and Cd(II) Complexes of HeptadentateAsymmetrical Tripodal Schiff Base - Salehzadeh, Sadegh; Keypour, Hassan (Asian Journal of Chemistry, 2010)
Bis(2-aminoethyl)(3-aminopropyl)amine, 2-pyridinecarboxalde-hyde and a number of metal ions were used to prepare metal complexes of tripodal Schiff base ligand (L322). The resulting complexes, [M(L322)](ClO4)2 [M = Mn(II), Ni(II), Cu(II), Zn(II) and Cd(II)]; L322N[CH2CH2CH2N═CH(C5H4N)][(CH2CH2N═CH(C5H4N)]2, were characterized by microanalysis and IR spectra in all cases and by nothing sup 1H NMR spectra in the case of Zn(II) and Cd(II) complexes. In the nothing sup 1H NMR spectrum of the cadmium complex the signals of imine protons having two clear satellite peaks (3J = 44.41–47.64 Hz) with rarely observed intensities in the ratio 1 : 6 : 1 due to coupling with neighbouring 111/113Cd. The ab initio studies on [Zn(L322)]2+ and [Cd(L322)]2+ complexes were also reported. The results show that the most bonding interaction between the metal ion and the bridging tertiary nitrogen atom of ligand occurs in the Cd(II) complex.